Differential transcriptome analysis of different resistant citrus varieties infected with wild-type and toxin synthesis-impaired strains causing Alternaria brown spot - MA Hui; MA Haijie; JIAO Chen; LI Hongye (浙江大学学报. 农业与生命科学版, 2023)
To investigate the differences in the response of citrus varieties with different resistances to Alternaria citri toxin (ACT) during interaction with the Alternaria alternata pathotype tangerine causing Alternaria brown spot, we inoculated the wild-type toxin-producing strain Z7 and the ACT synthesis-impaired mutant strain ΔΔACTT6 onto the leaves of resistant variety Clementine (Citrus clementina Hort. ex Tan. cv. Clementine) and the susceptible variety Dancy (Citrus reticulata Blanco cv. Dancy), and analyzed the gene expressions at 24 h and 48 h after inoculation using transcriptome sequencing technology. By comparing the corresponding differences in transcription between the two citrus varieties against the toxin-producing and non-toxin-producing strains, we found that the genes involved in the pathogen-associated molecular patterns (PAMPs)-triggered immunity (PTI) and effector-triggered immunity (ETI) pathways, pathogenesis-related proteins, WRKY transcription factors, and the secondary metabolic pathway were induced by the toxin-producing strain in both the varieties. At the later stage of inoculation (48 h), the toxin-producing strain mainly activated macromolecular degradation processes such as lipid and protein degradation in the susceptible citrus variety, indicating that its cellular integrity was disrupted due to toxin production, whereas the resistant citrus variety was mainly enriched in biological processes such as detoxification and jasmonic acid metabolism. Some multidrug and toxic compound extrusion protein (MATE) genes were specifically activated in the resistant citrus variety, which implies their ability to resist fungal toxins. In conclusion, the molecular regulatory mechanisms and key functional genes involved in the response of citrus varieties to ACT are preliminarily clarified, which provide a theoretical basis for the molecular breeding of citruses against Alternaria brown spot.